PAS to form new opposition bloc - New, Straits Times (Sabah) (New Straits Times, 2016)
PAS' announcement that it will form a new political partnership with friendly parties will transform the national political landscape. 'This means that the country will now have a second opposition bloc. Analysts expect this to benefit Barisan Nasional as voters will conclude that these opposition groups are fragile and weak. Be that as it may, Umno Vice president Datuk Seri Dr Ahmad Zahid Hamidi says the party has to work three times harder and smarter